Assessing the financial burden of hemodialysis treatment in Malaysia - Mohd Fadzli, Nur Fatin Aqilah; Mohd Rasani, Ali Aminuddin; Keng, Soon Lean (Belitung Raya Foundation, Indonesia, 2021)
Background: Patients with chronic kidney disease (CKD) spend substantial money on hemodialysis (HD) treatment. The growing intersection between socioeconomic status and financial burden represents an emerging challenge to the CKD community. Objective: This study assessed the financial burden of HD treatment on patients at a Malaysian tertiary teaching hospital. Methods: A cross-sectional study was carried out in the HD unit at a Malaysian tertiary teaching hospital from January to February 2021. Patients undergoing HD were purposively selected. A self-administered questionnaire was used to collect data on socio-demographic, finances, the patient's health history, treatment costs, and healthcare utilization. In addition, Pearson Chi-Square tests were used to analyze the data. Results: A total of 100 patients receiving HD treatment were included in the study. The mean age was 62.06 years (SD = 27.50), with 52% reporting moderate financial burdens. The financial burden was associated with employment status, salary, and income class among HD patients (p <0.05). Conclusion: Evidence showed a large proportion of Malaysian patients receiving HD treatment came from the B40 income bracket. The findings indicate that financial burdens can impact HD patients and are related to employment status, salary, and income class. Therefore, the ability to identify HD patients' financial needs is critical in nursing practice.